The influence of shame on status consumption with restorative tendency as shame response within a Chinese context - Chen, Yanyan (2018)
Shame is a universal but painful emotion which is known to most people. Major research reported in the shame literature has focused on the response to shame within the behavioral tendencies of withdrawal (Dickerson, Gruenewald & Kemeny, 2004; Kemeny, Gruenewald & Dickerson, 2004; Tangney, Mashek & Stuewig, 2005), and of externalization (Baumeister, Smart & Boden, 1996; Bushman & Baumeister, 1998; Tangney, Wagner, Fletcher & Gramzow, 1992). Recent discussion on shame response suggests that shame also leads to a restorative tendency through self-improvement and enhancement (Gausel, Leach, Vignoles & Brown, 2012). This is a result of most previous studies being conducted within a Western context where cultures devalue shame and see it as a totally negative emotion which should be avoided. Conversely, Eastern cultures are shame-affirming cultures and often see shame as a motivation for improvement. These different attitudes towards shame and different behavioral tendencies have recently been discussed in the shame literature (Skeikh, 2014). However, Sheikh (2014) provides only a conceptual idea of the shame response of restorative tendency, while lacking support from empirical evidence. This gap is important, yet poorly studied by researchers. To bridge the gap, this research aims to examine shame and its response of restorative tendency by providing qualitative evidence with linguistic examples of a shame restorative tendency. Further, though existing studies pay significant attention to the role of shame in regulating one’s behavior, most consider it in terms of the negativity of withdrawal and externalizing tendencies (Cohen, Wolf, Panter & Insko, 2011; Tangney, et al., 1992; Tangney & Dearing, 2002). Few recent studies focus on shame’s restorative role in regulating behavior (Tangney, Stuewig & Martinez, 2014). Additionally, most of these studies limit their focus within fields such as psychology (Scheff, 2014) and sociology (Gilbert, 2003). Research on the impact of shame in the consumption field is scarce. Therefore, following recent discussion on shame restorative tendency, and aiming to supplement existing knowledge on shame in consumption behavior, this research adapts self-affirmation theory and self-regulation theory in investigating the influence of shame in the context of status consumption. The research employs a mixed method using both qualitative and quantitative approaches. Incorporating a linguistic corpus analysis, the qualitative approach allows the investigation of the concept of shame and its causes and responses with Chinese and English corpus. Linguistic evidence supports the mainstream view of shame (Tangney, Miller, Flicker & Barlow, 1996; Tangney & Dearing, 2002) where self-attack is a cause of shame, and withdrawal and externalizing behaviors are responses to shame. More importantly, it confirms the alternative response to shame with restorative tendency raised in recent discussions (Gausel, et al., 2012; Sheikh, 2014), and provides substantial examples of restorative behaviors. Following this, a paper-based survey questionnaire distributed to Chinese consumers (n=210), aims to test the impact of shame on the consumption field with its response of restorative tendency. Stepwise hierarchical regression results highlight the influence of shame on consumer status consumption. It shows that consumers with high shame proneness are more likely to participate in status consumption, but only under the condition of a high independent construal of the self. To further examine the linkage between shame and status consumption, we then conduct three experimental studies. Study 1 (n=106) aims to investigate the impact of feeling shame on status consumption. Results suggest that the group with aroused feelings of shame demonstrates a higher intention to purchase status products. Study 2 (n=114) aims to test whether shame impacts consumer’s preferences for conspicuousness when both products are considered as status products. Results in this study found that consumers with primed shame feelings show a higher preference for status products with high conspicuousness, i.e., loud products. Study 3 (n=125) explores the moderating effect on shame and status consumption due to the relationships between consumers and those who accompany them, i.e., psychological proximity to others. Results suggest that when a consumer is accompanied by someone with whom they have a close relationship, the consumer’s feelings of shame are more likely to transfer into status consumption since they place high importance on those significant others with whom they share psychological proximity, rather than those with whom they have distant relationships. This research extends the existing literature by testing the influence of shame on status consumption with its restorative tendency. The corpus analysis helps to advance our understanding of shame responses and confirm a restorative tendency as an alternative response to shame, rather than merely the withdrawal or externalizing tendencies drawn from Western literature. This research fills this gap by providing linguistic evidence of restorative actions as a shame response, and provides the preconditions for testing the impact of shame on status consumption in the quantitative approach which follows. Most importantly, the quantitative part of this research adds to the existing consumption literature with status consumption as a restorative tendency responding to shame. By applying self-affirmation theory and self-regulation theory to build the conceptual model, this research also broadens the theorist’s discernment of shame on status consumption by explaining the mechanism of shame with response restorative tendency, which then leads to status consumption. Further, findings from extended studies on the impact of shame on status consumption with conspicuousness and psychological proximity offer insights for advertising agencies or marketing organizations demonstrating the practical implications of shame appeals.